Convenient synthesis of N-1-alkyl benzimidazoles via Pd catalyzed C–N bond formation and cyclization. Issue 15 (3rd August 2021) - Bie, Fusheng; Yao, Yongfeng; Cao, Han; Shi, Yijun; Yan, Peng; Ma, Jie; Han, Ying; Liu, Xuejing
Abstract: N -1-Alkyl-2-unsubstituted benzimidazoles were directly synthesized by intermolecular coupling of formimidamides with benzylamines; the syntheses were catalyzed by Pd(OAc)2 in one pot, giving rise to moderate to good yields. Aromatic formamidines with various substituents as starting materials could be readily prepared from the reactions of the corresponding anilines and N, N -dimethylformamide dimethyl acetal in high yields. Graphical Abstract: UF0001